Kendala Penggunaan Bahasa Indonesia Pada Proses Pembelajaran di Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi. - Ika Febriana; Harry Mustary Purba; Ingat Berkat Giawa; Janter Andre Suman Hasibuan; Titus Manik (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to identify barriers to the use of Indonesian in the learning process in the Physical Education, Health and Recreation study program. To measure perceptions and experiences regarding the use of Indonesian in learning, especially in understanding technical content, providing teaching, and communicating between students. This research uses a quantitative approach method by distributing questionnaires to third semester students. The research results show that the majority of respondents think that using Indonesian is effective in understanding basic concepts, but it is difficult to understand technical terms in foreign languages. In addition, misunderstandings often occur between instructors and students, especially in teaching practice environments. Another barrier identified was the lack of specific vocabulary in Indonesian to explain complex concepts in the fields of sport and health. The results of this research indicate that there is a need to adopt terminology in Indonesian that is easier to understand and improve instructors' abilities in creating teaching materials in language that is easier to understand.